IMPLEMENTATION OF THE SAW METHOD ON EMPLOYEE ACHIEVEMENT DETERMINATION - Ikhlas Septi Ramadan; Eko Haryanto; Melva Sari Panjaitan (Sean Institute, 2022)
This company doesn’t influence identifying the best employees so they are not excited about having the highest employee ratings. The delay in the process of finding the best people can affect employee motivation. This results in the company taking a long time in overcoming the decisions made in identifying the best employees. Fraud occurs in identifying the best employees based on specified criteria. This is because companies that do not implement a decision support system properly and efficiently identify the best people in the company. A set of methods that perform evaluation modeling in each process to help managers make decisions is the definition of a decision support system. According to Turban, the data that will be processed in decision making has provided an interface to the user to make it easier to combine the results of thinking in making final decisions (Sari, 2018). In this study, by searching for the best employees to get a conclusion from the results of the calculation of the maximum value. The maximum value is V2, so alternative A2 are the alternative chosen as the alternative best. In other words, Sammy are the best employee.